Relaxer [videorecording (DVD)] - Potrykus, Joel; Potrykus, Joel; Potrykus, Joel; Burge, Joshua; Dastmalchian, David; Hyland, Andre (Oscilloscope Laboratories, 2019)
A young man tries to meet a challenge given to him that requires that he stays on the couch in his living room until he reaches the level 256 on Pac-Man.